Quantitation of the histological changes found in small intestinal biopsy specimens from children with suspected coeliac disease. Issue 1 (January 1974) - Risdon, R. A.; Keeling, Jean W.
Abstract : The histological appearances in 85 peroral small intestinal biopsies from children have been analysed quantitatively by the method of Dunnill and Whitehead (1972). As applied to such biopsy specimens, this technique provides indices of both the mucosal volume and of the mucosal surface-to-volume ratio. When compared with controls, `flat' biopsies from children with untreated coeliac disease invariably showed much smaller surface-to-volume (c:lh) ratios. The mucosal volumes (h) of these biopsies were, however, significantly increased. Specimens showing less marked abnormalities (socalled `partial villous atrophy') had c:lh ratios in an intermediate range, but, like the biopsies from untreated coeliacs, h values were significantly increased. In morphologically normal biopsies correlation of surface-to-volume ratios with age showed that c:lh ratios were significantly smaller in younger children. Some of these lower c:lh ratios overlapped the range observed in abnormal biopsies showing partial villous atrophy. However, in the atrophic biopsies additional histological changes, such as abnormalities of the surface epithelial cells and an increased inflammatory cell infiltration of the lamina propria, were invariably present. Slight changes in biopsies from children under 2 years of age should, therefore, be interpreted cautiously, and should not necessarily be regarded as pathological on the evidence of the villous pattern alone. The quantitative technique employed proved reproducible under normal working conditions, and its greatest practical value would appear to be in following accurately serial changes in biopsies from the same patient.